Dissection of quantitative trait nucleotides and candidate genes associated with agronomic and yield-related traits under drought stress in rapeseed varieties: integration of genome-wide association study and transcriptomic analysis - Salami, Maryam; Heidari, Bahram; Alizadeh, Bahram; Batley, Jacqueline; Wang, Jin; Tan, Xiao-Li; Dadkhodaie, Ali; Richards, Christopher (Frontiers in Plant Science, 2024)
An important strategy to combat yield loss challenge is the development of varieties with increased tolerance to drought to drought tolerance to maintain production. Improvement of crop yield under drought stress is critical to global food security. In this study, we performed multiomics analysis in a collection of 119 diverse divers' rapeseed (Brassica napus L.) varieties to dissect the genetic control of agronomic traits in two watering regimes [well-watered (WW) and drought stress (DS)] for three years. In the DS treatment, irrigation continued till 50% pod development stage whereas in the WW condition, it was performed throughout the whole growing season. Results of genome-wide association study (GWAS) using 52,157 single nucleotide polymorphisms (SNPs) revealed 1,281 SNPs associated with traits. Six stable SNPs showed sequence variation for flowering time between the two irrigation conditions across years. Three novel SNPs on chromosome C04 for plant weight were located within of drought tolerance-related gene ABCG16, and their pleiotropically effects on seed weight per plant and seed yield were characterized. We identified the C02 peak as a novel signal for flowering time, harboring 52.77% of the associated SNPs. The 288 kbps LD decay distance analysis revealed 2,232 candidate genes (CGs) associated with traits. The CGs BIG1-D, CAND1, DRG3, PUP10, and PUP21 involved in phytohormone signaling and pollen development with significant effects on seed number, seed weight and grain yield in drought condition. By integrating GWAS and RNA-seq, 215 promising CGs were associated with developmental process, reproductive processes, cell wall organization, and response to stress. GWAS and differentially expressed genes (DEGs) of leaf and seed in the yield contrasting accessions identified BIG1-D, CAND1, and DRG3 genes for yield variation.Results of our study provide insights into the genetic control of drought tolerance and the improvement of marker-assisted selection (MAS) for breeding high-yield and drought tolerant varieties.